An exploration of how community‐dwelling older adults enhance their well‐being. (26th August 2019) - Waterworth, Susan; Raphael, Deborah; Gott, Merryn; Arroll, Bruce; Benipal, Jagpal; Jarden, Aaron
Abstract: Aim and objectives: To explore community‐dwelling older adults approaches to enhancing their psychological well‐being. Background: Older adults who are living with long‐term or chronic health conditions are particularly at risk of experiencing low psychological well‐being. Little attention has been paid to preventive strategies that enhance psychological well‐being and, in particular, to understanding how older adults enhance their own well‐being. Methods: Using Seligman's PERMA model of well‐being (2011) as an organisational framework, this qualitative study interviewed 48 older people aged between 66 and 99 years. Of these, 17 men and 20 women participated in semi‐structured interviews. Additionally, 11 women, all widows with a mean age of 81 years, participated in a focus group. The data were analysed with reference to the five aspects of PERMA (Positive emotion, Engagement, Relationships, Meaning, Accomplishment) with a focus on identifying what actions the older people were taking to enhance their well‐being. Further analysis involved coding the data into processes or practices and also influencing factors. Findings: Most participants used a range of strength‐based strategies or practices to enhance their well‐being. For a small number of participants ( n  = 3), these practices were supported by the presence of partners as carers. However, using PERMA as our conceptual model illustrated that despite Seligman's view that individuals can take positive action within each of the five aspects of PERMA to enhance well‐being, external factors, for example economic circumstances or mobility, can influence the ability of older adults to undertake well‐being practices. Conclusions: Older adults have a range of strategies or practices that they use to enhance their well‐being. However, well‐being is not a static concept and it is important to recognise the influence of health, social and environmental factors as enablers and enhancers of well‐being. Implications for practice: Nurses can play a central role in supporting older adults who may be at risk of lower well‐being. Nurses can do this by developing interventions to enhance well‐being and ensuring better person‐activity fit of strategies and practices. Our findings support the need for nurses to be involved in providing opportunities for older people to discuss well‐being to support the development of individual, as well as community, models of well‐being.